2013
DOI: 10.4103/0259-1162.118979
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic effect of two different doses of fentanyl in combination with bupivacaine for surgical site infiltration in cases of modified radical mastoidectomy: A double blind randomized study

Abstract: Background:Limited evidence supports the efficacy of peripheral route fentanyl and local anesthetic combination for postoperative analgesia. Our study was therefore designed to demonstrate the analgesic efficacy of two different doses of fentanyl in combination with bupivacaine for surgical site infiltration in patients undergoing modified radical mastoidectomy (MRM).Materials and Methods:60 patients undergoing MRM under general anesthesia were randomly allocated into two groups, first group receiving 0.5% bup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The other modalities for pain relief in patients undergoing mastoidectomy include local infiltration and greater auricular nerve (GAN) block. Bhandari G et al [ 17 ] administered 12 mL infiltration both after the incision and just before completion of modified radical mastoidectomy with a combination of bupivacaine and fentanyl 50 or 100 μg. The authors observed that patients receiving fentanyl 100 μg had lower VAS score as compared to patients requiring fentanyl 50 μg at 4 and 6 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The other modalities for pain relief in patients undergoing mastoidectomy include local infiltration and greater auricular nerve (GAN) block. Bhandari G et al [ 17 ] administered 12 mL infiltration both after the incision and just before completion of modified radical mastoidectomy with a combination of bupivacaine and fentanyl 50 or 100 μg. The authors observed that patients receiving fentanyl 100 μg had lower VAS score as compared to patients requiring fentanyl 50 μg at 4 and 6 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Five RCTs reported on perioperative pain management for tympanomastoid surgery (Table ) . Pain was scored using a VAS, WBS, or a customized OPS.…”
Section: Resultsmentioning
confidence: 99%
“…Bhandari et al found that the combination of bupivacaine and 100 μg fentanyl for operative field infiltration was associated with better postoperative analgesia than the combination with 50 μg fentanyl . In both study groups the VAS score was <3 at each time interval, and the bupivacaine + fentanyl 100 μg group had lower VAS scores than the bupivacaine + fentanyl 50 μg group at all time intervals . Nalini et al investigated intramuscular lornoxicam 8 mg twice daily versus diclofenac 75 mg twice daily following radical mastoidectomy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapun golongan non-opioid terdiri dari golongan salisilat, asam asetat, cyclooxygenase-2 (COX-2) inhibitor, fenamat, asam proprionat, asetaminofen, dan pirazolon. 16 Pemberian analgesik yang dimulai sejak hari pertama pascatonsilektomi telah diteliti dapat meringankan nyeri. 14 World Health Organization (WHO) telah mengeluarkan pedoman terbaru untuk mengatasi nyeri yang disebut New Adaptation of WHO Analgesic Ladder.…”
Section: Gambar 1 Modifikasi Wong-baker Faces Pain Rating Scale (Wbfs)unclassified